PENINGKATAN KESADARAN PEREMPUAN TERHADAP PENGELOLAAN LINGKUNGAN WILAYAH PESISIR DI KELURAHAN BUMI WARAS BANDAR LAMPUNG - Darmastuti, Ari; Budiono, Pitojo; Maryanah, Tabah; Handayani, Dwi Wahyu (Prosiding Pengabdian FISIP Unila, 2012)
Can  be formulated  conditions  of coastal communities  Bandar  Lampung, especially  in the Village Earth Sane, as follows:  (1). Women and children are the most vulnerable due to  unhealthy environmental conditions, (2). Knowledge and awareness of  the community, especially women in  the surrounding  environment management  is still low, (3). Women and children are  the most vulnerable due to weak  family economy,  so the  sustainability of  low  education  and women  easily become victims of domestic violence. The method used in this activity is a seminar / lecture on organizational functions,  strengthening organizations,  gender  and the environment, human rights and  the environment,  and the  law on  the environment.   This activity is  also  using simulation methods on how to build  a strategy of analysis of the problem and  its potential,  as well as  simulations of  effective  environmental management measures. The results of  the activities, participants  gain  understanding  about  the organization  /  institution,  gender  and the  environment, human rights  and the environment and socialization of Environmental Law.                                                                                                                                            Keywords: Awareness of Women, Environmental Management, Gender